Exploring Students’ English Learning Engagement in Wordwall-Based Activities - Khalifah Nurul Hikmah; Kamelia Lutviyani; Natasha Sayyida; Syauki (Universitas Islam Negeri Palopo, 2025)
Students’ engagement is a key factor in successful English language learning, yet many EFL learners in Indonesia still demonstrate low levels of engagement and often perceive English as difficult. This is perhaps due to a lack of interactivity in more traditional teaching approaches, which may discourage more active participation. Most previous studies on gamification in language learning focused on experimental studies using popular platforms like Quizizz and Kahoot, and there is also limited research on Wordwall in the Indonesian EFL context. This research gap highlights the need to explore how Wordwall can foster students’ learning engagement in English classrooms. This study aims to explore students’ emotional, behavioral, and cognitive dimensions of engagement in an English lesson that incorporates Wordwall activities. This study employed a qualitative descriptive method, involving two classes of 7th grade students in SMP Dharma Karya UT, South Tangerang, involving 42 seventh-grade students, with 10 students participating in semi-structured interviews in Indonesian formal classroom settings. Data were collected through two classroom observation sessions over a two-week period, supported by semi-structured interviews. The findings reveal that students demonstrated high emotional engagement through enthusiasm and enjoyment, behavioral engagement through active participation and peer collaboration, and cognitive engagement through recalling vocabulary, constructing sentences, and explaining their answers during Wordwall-based activities. Despite promoting enjoyment, meaningful engagement was strengthened when Wordwall was accompanied by appropriate instructional guidance. These findings contribute to the discussion on gamification in English language education by highlighting how Wordwall can be strategically integrated to support sustained emotional, behavioral, and cognitive engagement, rather than merely increasing classroom enjoyment.